Scientific basis for power training - Hoffman, J. R. (EWF Scientific Magazine, 2016)
An important factor for maximizing power production is exerting as much force as possible in a short period of time. Training for maximal strength through heavy resistance training may be effective for enhancing power in the inexperienced athlete, but may not provide the same stimulus in the experienced, resistance trained athlete. For these athletes, if plyometric exercises or a combination of plyometric and resistance training (using a light resistance such as might be used with ballistic training) is added to the training program, the athlete`s ability to increase their rate of force development may be enhanced. However, it is also important to understand that it is not a question of performing one mode of training versus the other, but it is a function of adding to the existing training program. In order to maintain strength performance the athlete needs to continue to provide the stimulus that maintains maximal strength performance. However, the inclusion of specific exercises that focuses on high velocity movements will maximize power performance as well. This has also has been demonstrated by several investigations that have shown that the inclusion of ballistic exercises (e.g. squat jump) can enhance power production in resistance-trained athletes when combined with their regular traditional resistance training programs (Hoffman et al., 2005; Newton et al. 1999). The use of ballistic training appears to generate a new window of adaptation stimulating performance gains in elite athletes with considerable training experience. The use of plyometric, ballistic and Olympic exercises has been demonstrated to be advantageous in the training programs of experienced, resistance trained athletes interested in maximizing power.